Relationship Of Income Expectations With Entrepreneurial Interests In Students Of The Family Welfare Education Study Program - Nailulazmi, Velia; Yulastri, Asmar (Jurnal Pendidikan Tata Boga dan Teknologi, 2023)
The background of this research is most students think that the income of an entrepreneur is erratic and low. This causes a lack of student entrepreneurship interest. The research objectives were to describe: 1) student expectations of entrepreneurial income, 2) student entrepreneurial interest, 3) analyze the relationship between entrepreneurial income expectations and entrepreneurial interest in students of the Family Welfare Education Study Program. This type of research is quantitative with a correlational approach. The research population was 142 students of the Family Welfare Education Study Program class of 2018. The sample is 60 people taken by Proportionate Random Sampling. The data collection technique uses a questionnaire distributed via Google Form. Data analysis using descriptive analysis and correlational analysis. The results showed that: 1) the level of students' expectations of entrepreneurial income was in the medium category with a range of 55–70 (55%), 2) the level of student entrepreneurship interest was in the low category with a range of 40-55 (40%), 3) there was a positive and significant relationship between students' expectations of entrepreneurial income and entrepreneurship interest with a correlation value of rxy 0.677 means that it has a strong level of relationship and tcount (7.005) > ttable (2.0017). This means that the higher students' expectations of entrepreneurial income, the higher the entrepreneurship interest for students of the Family Welfare Education Study Program, Padang State University.